An anti-tuberculosis compound screen using a zebrafish infection model identifies an aspartyl-tRNA synthetase inhibitor - Eva Habjan; Vien Q. T. Ho; James Gallant; Gunny van Stempvoort; Kin Ki Jim; Coen Kuijl; Daan P. Geerke; Wilbert Bitter; Alexander Speer (The Company of Biologists, 2021)
Finding new anti-tuberculosis compounds with convincing in vivo activity is an ongoing global challenge to fight the emergence of multidrug-resistant Mycobacterium tuberculosis isolates. In this study, we exploited the medium-throughput capabilities of the zebrafish embryo infection model with Mycobacterium marinum as a surrogate for M. tuberculosis. Using a representative set of clinically established drugs, we demonstrate that this model could be predictive and selective for antibiotics that can be administered orally. We further used the zebrafish infection model to screen 240 compounds from an anti-tuberculosis hit library for their in vivo activity and identified 14 highly active compounds. One of the most active compounds was the tetracyclic compound TBA161, which was studied in more detail. Analysis of resistant mutants revealed point mutations in aspS (rv2572c), encoding an aspartyl-tRNA synthetase. The target was genetically confirmed, and molecular docking studies propose the possible binding of TBA161 in a pocket adjacent to the catalytic site. This study shows that the zebrafish infection model is suitable for rapidly identifying promising scaffolds with in vivo activity.